SOSIALISASI BAHAYA PENYALAHGUNAAN NARKOBA BAGI PESERTA DIDIK SMA NEGERI 1 PANGEAN KABUPATEN KUANTAN SINGINGI - Nurdiansyah Nurdiansyah; Gepria Arnise; Wiwing Apriliansyah; Guritno Dimas Hadi; Widya Andini; Anggea Selvitra; Amelia Syafitri; Sri Puspita; Tantrike Helsa; Fitri Wahyuna; Ardhelia Safitr (Bajang Institute, 2022)
The purpose of socialization of the dangers of drugs in high SMA N 1 Pangean Kuantan Singingi so that participants can know and understand the impact of drug use both physically and psychologically. Drug abuse is increasing day by day. The danger of drugs is a threat to the younger generation and can cause dependence. In this modern era of sophisticated drugs become a problem for mankind in various parts of the Earth. Therefore, through the socialization of the dangers of drugs is able to improve the understanding of SMA N 1 Pangean about the types of narcotics, the impact of drug use that can damage physical and psychological health and how to prevent and overcome drug abuse among adolescents. With a lot of knowledge and good about the dangers of drugs, it is expected to be able to provide information in order to suppress the rise of drugs. For this reason, this socialization activity can provide understanding to adolescents so that they can fortify the younger generation from drug abuse.